The effects of entrepreneurial resources on the allocation of entrepreneurial effort in Gauteng SMME Sector - Mampuru, Alice Khantso (My University, 2020)
Past research looked at the contribution of the small business sector in economic development. Some literature suggested that the performance of this sector continued to face challenges that are attributable to SMME characteristics such as demographic profiles of individual entrepreneurs. Trivial research has focused on contextual issues affecting the SMMEs sector of South Africa. This research, therefore, took a closer look at the effects of entrepreneurial resources (context) on the allocation of entrepreneurial effort in an attempt to understand how these variables applied in South Africa's SMMEs sector. Using a quantitative approach, the study collected data from a sample of 206 SMME operators. Through empirical scrutiny, this study found that demographic profiles of entrepreneurs had a significant role in explaining the variance in the allocations of entrepreneurial effort. Taken with internal entrepreneurial resources, a modest yet significant variance was explained in the allocation of entrepreneurial effort. Empirical results, however, rejected the hypothesis that external resources negatively influenced the allocation of entrepreneurial effort. While a positive yet insignificant amount of variance in value creation could be explained by external entrepreneurial resources, a strong and significant variation in value appropriation was found to be associated with external resources. The study further found that resource combinations had a positive effect on the allocation of entrepreneurial effort. Policymakers can benefit significantly from this research in their efforts to formulate a policy that is indigenous to specific contexts. Practitioners can use the insights gained from this research to elucidate and measure entrepreneurial outcomes. This could improve the processes and mechanisms used in entrepreneurship ecosystem development. This study makes a unique and significant contribution to the ongoing debate about the role of context in the allocations of entrepreneurial effort. It further appreciates the significant contribution of Baumol’s Theory of Entrepreneurship allocations in explaining the phenomenon, making a unique contribution to the vast knowledge about contextual influences on the allocations of entrepreneurial effort.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Entrepreneurship allocations; Emerging markets; Context; Value-based entrepreneurship; SDG-8: Decent work and economic growth